2009
DOI: 10.1080/14765280902847734
|View full text |Cite
|
Sign up to set email alerts
|

Cost efficiency analysis in banking industries of ten Asian countries and regions

Abstract: Despite the great achievement of three decades of economic reform, the Chinese banking sector takes the blame for its dysfunctional system, especially the large amount of non-performing loans. The ease of foreign banks' entry set by the WTO from December 2007 raises our concern of the capability of domestic banks to compete against foreign Asian banks. This study attempts to address this issue by measuring the cost efficiency of ten major Asian banking industries from 1998 to 2005 using panel data stochastic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…As we noted earlier, previous research has demonstrated that similar models find a positive shadow return on equity prior to the financial crisis (e.g., Boucinha et al 2009;Hughes et al 2001;Shen et al 2009), confirming that overleveraged banks display the highest positive shadow return on equity in the years preceding financial crisis. In strong contrast, the results for Turkey in the post-financial crisis period, when the banking system was being strongly recapitalized, show that the shadow return on equity is negative in all six of the models estimated (see Table 2).…”
Section: Resultssupporting
confidence: 74%
“…As we noted earlier, previous research has demonstrated that similar models find a positive shadow return on equity prior to the financial crisis (e.g., Boucinha et al 2009;Hughes et al 2001;Shen et al 2009), confirming that overleveraged banks display the highest positive shadow return on equity in the years preceding financial crisis. In strong contrast, the results for Turkey in the post-financial crisis period, when the banking system was being strongly recapitalized, show that the shadow return on equity is negative in all six of the models estimated (see Table 2).…”
Section: Resultssupporting
confidence: 74%
“…The selection of inputs and outputs follows the recent empirical studies on bank efficiency (See Matousek et al (2014), Assaf et al (2013), Shen et al (2009)). Thus, to estimate TE and CE using the DEA, we employ as input variables: total number of employees, fixed assets, and deposits.…”
Section: Datamentioning
confidence: 99%
“…al. (2009), Fu and Heffernen (2008), Matthews et al (2007) 3 Fu and Heffernen (2007), Shen et al (2008), Matthews et al (2007) underutilization of factors is consistent with the notion of X-inefficiency, but the wrong factor-mix is indicative of long-standing employment constraints imposed on the banking system in the pre-reform period. Insofar as allocative inefficiency can be explained as the result of official employment constraints, the implied cost inefficiency cannot be viewed as a management deficiency but a rational outcome of optimizing behaviour.…”
Section: Introductionmentioning
confidence: 61%